1991
DOI: 10.1104/pp.97.1.366
|View full text |Cite
|
Sign up to set email alerts
|

Germin-Like Polypeptides Increase in Barley Roots during Salt Stress

Abstract: The 26 kilodalton, isoelectric point 6.3 and 6.5 (Gsl and Gs2) polypeptides that increase in barley (Hordeum vulgare L.) roots during salt stress were isolated and identified. Both Gsl and Gs2 had high sequence similarity to germin, a protein that increases significantly in germinating wheat seeds. Like germin, Gsl and Gs2 were resistant to proteases and were glycosylated. lmmunoblots were probed with antibodies to Gs1 and Gs2 to determine the distribution of these polypeptides among organs and cell-free fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 36 publications
2
60
1
2
Order By: Relevance
“…In young seedlings (3 d of growth) the enzyme is localized in the mature region of the root epidermis as well as in the coleorhiza, in accordance with the work of Hurkman et al (1991). However, after 10 d of growth the activity was found only in the coleorhiza and was not detectable in roots.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In young seedlings (3 d of growth) the enzyme is localized in the mature region of the root epidermis as well as in the coleorhiza, in accordance with the work of Hurkman et al (1991). However, after 10 d of growth the activity was found only in the coleorhiza and was not detectable in roots.…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that several germin isoforms are induced during the development and germination of wheat embryos (Grzelczak and Lane, 1984;Grzelczak et al, 1985;Lane et al, 1987Lane et al, , 1992, as well as in roots of salt-stressed barley plants (Hurkman et al, 1991(Hurkman et al, , 1994. Since only the wheat germin isoform G has been shown to be an oxalate oxidase (Lane et al, 1993), it remains unclear whether all these germin isoforms possess oxalate oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous functions have been proposed for GLPs, including desiccation and hydration (39), restructuring of cell walls (13), salt and heavy metal response (40), and plant defenses (15,41,42). Because GLPs represent a large family of extracellular proteins, some of which have superoxide dismutase activity, we propose a novel function for these proteins in mediating the oxidative burst during the wound response.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat germin is expressed in partially hydrated (60% water) germinating embryos (Lane et al, 1991). The function of this protein is not known; however, a polypeptide from barley that is specifically salt-stress inducible (Hurkman et al, 1991) has a high sequence similarity to it. Germin also has moderate amino acid similarity to spherulins of Physanum polycephalum, proteins expressed if plasmodia are subjected to environmental stresses, including osmotic and temperature extremes (Lane et al, 1991).…”
Section: Discussionmentioning
confidence: 99%